Students' Reflective Thinking on The Topic of Protozoa - Citraningrum, Mivtha; Machmud, Amir (Islamic Journal of Integrated Science Education (IJISE), 2024)
One of the materials studied in science learning is about the Filum Protozoa (one of the invertebrate animals). Students only know that protozoa generally cause harm to humans or animals because they are parasites but do not think about what the solution to overcome this parasite is. To overcome this, students are encouraged to have reflective thinking skills. Reflective thinking is the ability of individuals to select knowledge that they have acquired, which is relevant to the purpose of the problem and utilize it effectively in problem solving. To develop reflective thinking skills, we can use learning strategies that can sharpen students' thinking skills. The purpose of writing this article is to find out how experts think about reflective thinking, how to measure reflective thinking and how to develop reflective thinking skills in students. The method used in this research is a literature study, in the form of analysis and synthesis of several scientific articles. How to measure reflective thinking can be done with tests and non-tests. Researchers collected 10 previous studies in the range of 2011-2018 regarding reflective thinking skills then analyzed and concluded that reflective thinking is a student's ability to select knowledge that has been owned and stored in his memory to solve any problems faced to achieve his goals.